Tinjauan Yuridis Penanggulangan Cyber-Recruitment dalam Tindak Pidana Perdagangan Orang: Tinjauan Unsur dan Pembuktian Digital - Gloria Carvallo; Soni Esrayanus Benu (Majelis: Jurnal Hukum Indonesia, 2026)
Human Trafficking (TPPO) has undergone a significant transformation in its modus operandi alongside the massive use of information technology, giving rise to the phenomenon of cyber-recruitment within the online scam industry. This study aims to analyze the juridical construction of the criminal elements in the cyber-recruitment modus operandi based on Law Number 21 of 2007, and to evaluate the potential disharmony of norms between the TPPO regulation and the Electronic Information and Transactions Law (UU ITE) regarding the regulation of digital evidence. The research method employed is normative legal research with a statutory approach and a conceptual approach. The results indicate that, dogmatically, the elements of TPPO—comprising the process of virtual recruitment, the means of fraudulent job promises, and the purpose of digital forced labor exploitation—under Law No. 21 of 2007 remain relevant for prosecuting cyber-recruitment perpetrators, although it demands a broader legal interpretation of cyberspace realities. However, legal certainty issues were found due to the lack of synchronicity in the regulation of digital evidence, where differences in procedures and qualifications exist between electronic evidence in the TPPO Law and the evidentiary standards in the UU ITE, which are volatile in nature. The implications of this research conclude the need for regulatory synchronization through the establishment of technical guidelines for handling TPPO-specific electronic evidence to provide a solid legal foundation for law enforcement agencies. This step is crucial to overcome cross-border jurisdictional obstacles and to ensure substantive justice and comprehensive protection of victims' rights in the digital era.